Dysfunction of different cellular degradation pathways contributes to specific β‐amyloid42‐induced pathologies. Issue 3 (3rd January 2018) - Ji, Xuan‐Ru; Cheng, Kuan‐Chung; Chen, Yu‐Ru; Lin, Tzu‐Yu; Cheung, Chun Hei Antonio; Wu, Chia‐Lin; Chiang, Hsueh‐Cheng
Abstract : The endosomal‐lysosomal system (ELS), autophagy, and ubiquitin‐proteasome system (UPS) are cel‐ lular degradation pathways that each play a critical role in the removal of misfolded proteins and the prevention of the accumulation of abnormal proteins. Recent studies on Alzheimer's disease (AD) pathogenesis have suggested that accumulation of aggregated β‐amyloid (Aβ) peptides in the AD brain results from a dysfunction in these cellular clearance systems. However, the specific roles of these pathways in the removal of Aß peptides and the pathogenesis underlying AD are unclear. Our in vitro and in vivo genetic approaches revealed that ELS mainly removed monomeric β‐amyloid42 (Aβ42), while autophagy and UPS clear oligomeric Aβ42. Although over‐ production of phosphatidylinositol 4‐phosphate‐5 increased Aβ42 clearance, it reduced the life span of Aβ42 transgenic flies. Our behavioral studies further demonstrated impaired autophagy and UPS‐enhanced Aβ42‐ induced learning and memory deficits, but there was no effect on Aβ42‐induced reduction in life span. Results from genetic fluorescence imaging showed that these pathways were damaged in the following order: UPS, autophagy, and finally ELS. The results of our study demonstrate that different degradation pathways play distinct roles in the removal of Aβ42 aggregates and in disease progression. These findings also suggest that pharmacologic treatments that are designed to stimulate cellular degradation pathways in patients with AD should be used with caution.—Ji, X.‐R., Cheng, K.‐C., Chen, Y.‐R., Lin, T.‐Y., Cheung, C. H. A., Wu, C.‐L., Chiang, H.‐C. Dysfunction of different cellular degradation pathways contributes to specific β‐amyloid42‐induced pathologies. FASEB J. 32, 1375‐1387 (2018). www.fasebj.org